THE ROLE OF ORGANIZATIONAL AMBIDEXTERITY IN ENHANCING INNOVATION IN MSME MARKETING PERFORMANCE - Utarsih, Henny (Faculty of Economic and Business, University of Pasundan, 2026)
This study examines the effects of organizational ambidexterity and innovation on the marketing performance of Indonesian coffee shop MSMEs. Using survey data from 203 MSMEs and analyzed with SEM-PLS, the findings reveal that innovation has a strong and significant positive effect on marketing performance, reflected in sales growth, customer satisfaction, and market expansion. In contrast, organizational ambidexterity does not have a significant direct impact on marketing performance. This result indicates that, in resource-constrained MSMEs, ambidexterity functions primarily as a supporting capability that sustains innovation rather than as a direct driver of market outcomes. The novelty of this study lies in demonstrating that ambidexterity’s contribution to MSME performance is predominantly indirect and context-dependent, particularly in service-based MSMEs within developing economies. The findings suggest that MSMEs should prioritize innovation as a core strategy to enhance marketing performance while maintaining ambidexterity to support long-term innovation sustainability.